Legal Review of Marriage for Divorced Women Outside the Religious Courts - Imam Sujono (International Journal of Islamic Thought and Humanities, 2022)
Marriage is a contract that justifies a man and a woman, with a marriage contract to build a happy and prosperous family. The marriage process has been regulated in Law Number 1 of 1974 that every marriage must be carried out according to religious provisions and must be recorded. But what about the marriage law for women who are divorced outside the religious court, according to Law Number 1 of 1974 and according to Islamic Law? Because in practice, there are also marriages that are carried out without recording so that they do not have a marriage certificate. Similarly, the occurrence of divorces that are not carried out in front of the Religious Courts, so they do not have a divorce certificate or certificate. For women who are divorced without having a divorce certificate who will enter into a new marriage. So, to legalize the marriage, one must apply for a marriage isbath for divorce.